THE EFFECT OF BUDGETING PARTICIPATION AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF LOCAL GOVERNMENT INSTITUTIONS - Elvira Zeyn; Nia Nuraeni (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
The study aims at determining the effect of budgetary participation and organizational commitment on the performance of local government institutions in Subang District SKPD. The sampling technique used was a survey method with a descriptive and verification approach with a type of questionnaire distributed to 27 SKPD in Subang Regency. Participation in budgeting had a significant effect on the performance of local government institutions while organizational commitment also had a significant effect on the performance of local government institutions in the SKPD of Subang Regency Government.